Pillar[5]arene-Based Fluorescent Sensor Array for Biosensing of Intracellular Multi-neurotransmitters through Host–Guest Recognitions - Mei, Yuxiao; Zhang, Qi-Wei; Gu, Qingyi; Liu, Zhichao; He, Xiao; Tian, Yang (Journal of the American Chemical Society, 2022)
Neurotransmitters are very important for neuron events and brain diseases. However, effective probes for analyzing specific neurotransmitters are currently lacking. Herein, we design and create a supramolecular fluorescent probe (CN-DFP5) by synthesizing a dual-functionalized fluorescent pillar[5]arene derivative with borate naphthalene and aldehyde coumarin recognition groups to identify large-scale neurotransmitters. The developed probe can detect seven model neurotransmitters by generating different fluorescence patterns through three types of host–guest interactions. The obtained signals are statistically processed by principal component analysis, thus the high-throughput analysis of neurotransmitters is realized under dual-channel fluorescence responses. The present probe combines the advantages of small-molecule-based probes to easily enter into living neurons and cross-reactive sensor arrays. Thus, the selective binding enables this probe to identify specific neurotransmitters in biofluids, living neurons, and tissues. High selectivity and sensitivity further demonstrate that the molecular device could extend to more applications to detect and image neurotransmitters.